The Effects of Servant Leadership, Occupational Commitment, and Work Engagement on Creativity of Teacher - Lindawati, Mega; Wulani, Fenika; Runtu, Julius (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study identifies the influence of servant leadership on teacher creativity. We considered occupational commitment and work engagement as sequential mediators in the relationship between servant leadership and teacher creativity. This current study uses surveys by distributing questionnaires to teachers at the